1998
DOI: 10.1017/s0043174500089670
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of glyphosate with chlorimuron, fomesafen, imazethapyr, and sulfentrazone

Abstract: Field experiments were conducted on eight weed species to determine if chlorimuron, fomesafen, imazethapyr, or sulfentrazone at two rates (labeled and one-half the labeled rate) were complementary tank mixtures with glyphosate at 210 and 420 g ai ha−1. Laboratory experiments were conducted on barnyardgrass, pitted morningglory, Palmer amaranth, and velvetleaf using radiolabeled glyphosate, chlorimuron, and imazethapyr to determine the absorption and translocation pattern of these herbicides applied alone and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
2
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 18 publications
(23 reference statements)
6
98
2
5
Order By: Relevance
“…Herbicide interactions have been extensively investigated and reported with respect to synergism, antagonism, and additivity (Colby 1967;Hatzios and Penner 1985). Previous research has demonstrated the benefit of utilizing reduced rates of selected soybean herbicides in mixtures to enhance weed control and diminish the development of resistant weed biotypes (Defelice et al 1989;Gressel 1990;Starke and Oliver 1998). However, little information has been published examining reduced rates of corn herbicides in mixtures for common lambsquarters control.…”
Section: Introductionmentioning
confidence: 99%
“…Herbicide interactions have been extensively investigated and reported with respect to synergism, antagonism, and additivity (Colby 1967;Hatzios and Penner 1985). Previous research has demonstrated the benefit of utilizing reduced rates of selected soybean herbicides in mixtures to enhance weed control and diminish the development of resistant weed biotypes (Defelice et al 1989;Gressel 1990;Starke and Oliver 1998). However, little information has been published examining reduced rates of corn herbicides in mixtures for common lambsquarters control.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of absorption and translocation of [ 14 C]glyphosate indicate that uptake occurs rapidly following application. In Echinochloa crus‐galli (L) Beauv, an annual weed which is susceptible to glyphosate, studies with [ 14 C]glyphosate have shown 50% of the radiolabel to be absorbed within 72 h of treatment, with 50% of the radiolabel distributed in the treated leaf, 19% in the roots and 31% translocated 4. Absorption and translocation of [ 14 C]glyphosate has been found to be less in plants at more advanced growth stages or under water stress 5.…”
Section: Introductionmentioning
confidence: 99%
“…However, antagonistic effects may occur in controlling some weed species due to the combination of these two active ingredients. Starke and Oliver (1998) reported that a mixture of glyphosate+ sulfentrazone was ineffective for barnyardgrass (Echinochloa crusgalli), palmer amaranth (Amaranthus palmeri), goosegrass (Eleusine indica) and ivy leafed morningglory (Ipomoea hederaceae) control. Here, when this mixture of herbicides was combined with both B sources, the percentage of control was lower in relation to the herbicide application without B, indicating no additive effect of these two herbicides with the two boron sources in controlling Euphorbia heterophylla and Bidens subalternans.…”
Section: Resultsmentioning
confidence: 99%